Therapist, Intermediary or Garbage Can? Examining Professional Challenges for School Social Work in Swedish Elementary Schools - Maria Kjellgren; Sara Lilliehorn; Urban Markström (International Journal of School Social Work, 2023)
The overall aim of this article is to describe and analyse critical components that influence the role and performance of school social workers in the Swedish elementary school. Special attention will be paid to aspects related to formal regulations, professional self-understanding, and SSWs’ role in the interplay between professional domains involved in elementary school. The data collection was conducted through four semi-structured qualitative focus group interviews with a total of 22 School Social Workers (SSWs) in four different regions in Sweden during the latter part of 2019. The results reveal three main challenges for the SSW: 1. To navigate in a pedagogic and medical arena within a multidisciplinary team, 2. To manage ambiguity without formal regulations and in unclear settings and leadership, and finally, 3. To negotiate tasks at different levels, with a health promotional and preventive focus. The SSW ends up, mainly, in remedial work with individual children. The results also disclose SSWs hold a vague professional self-understanding position with little formal mandate to perform their work. We suggest that national guidelines for SSWs be developed, and that a common base of knowledge and education be established.
Keywords: School social worker (SSW); multidisciplinary team; counselling; professional self-understanding; formal regulations